Constitutive expression of a gene encoding a polypeptide homologous to biologically active human platelet protein in Rous sarcoma virus-transformed fibroblasts. - Bedard, P A (1987)
A molecular clone corresponding to a 1.2-kilobase mRNA enriched in Rous sarcoma virus-transformed chicken embryo fibroblasts (CEF) was identified by differential screening of a cDNA library. The induction of the cloned sequence (denoted pCEF-4) in CEF infected by the temperature-sensitive mutant NY72-4 Rous sarcoma virus is rapid and independent of protein synthesis. DNA sequencing of the 1.2-kilobase insert of CEF-4 revealed an open reading frame that predicts an 11-kDa protein. The predicted pCEF-4 gene product is homologous to human connective tissue-activating peptide III (CTAP-III) and platelet factor 4 (PF-4). Serum stimulation of quiescent normal CEF results in a rapid but transient expression of pCEF-4 mRNA. Hence, pCEF-4 mRNA is expressed at the G0-G1 transition and during the first G1 phase of normal CEF reentering the cell cycle. The expression of pCEF-4 mRNA in Rous sarcoma virus-transformed CEF appears to be the result of transcriptional activation and stabilization of the transcript.